Odpowiedzi

2010-04-14T16:40:27+02:00
A) -3x=2x-10
-x=10 /:(-1)
x=-10
B) 2x - 2 = 7-x
3x = 9 /:3
x=3
C) 10=4-2x
2x=-6 /:2
x=-3
D)-(2x-1)=4
-2x = 3 /:(-2)
x=-3/2= -1 1/2
E) 2(x+1) = 6
2x = 4 /:2
x=2
1 5 1
Najlepsza Odpowiedź!
  • uire
  • Rozwiązujący
2010-04-14T16:42:09+02:00
A) -3x=2x-10
-5x=-10
x=2
b) 2x - 2 = 7-x
3x=7+2
3x=9
x=3
c) 10=4-2x
10-4=-2x
-2x=6
x=-3
d) -(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3
x=-3/2
e) 2(x+1) = 6
2x+2=6
2x=6-2
2x=4
x=2
2010-04-14T16:44:16+02:00
A) -3x=2x-10
-3x-2x=-10
-5x=-10/:(-5)
x=2
b)2x-2=7-x
2x+x=7+2
3x=9 /:(3)
x=3
c)10=4-2x
2x=4-10
2x=-6 /:(2)
x=-3
d)-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3 /:(-2)
x=-1,5
e) 2(x+1)=6
2x+2=6
2x=6-2
2x=4 /:(2)
x=2